Enhancing Flood Impact Analysis through the Integration of Landsat and MODIS Imagery - Tran Vu Van Hoa; Thien Chi Nguyen; Tung Thanh Truong; Tuan Anh Nguyen; Hoang Bao Lam; Son Thai Dang (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This article explores the efficacy of integrating Landsat and MODIS satellite imagery for comprehensive flood impact analysis. By employing advanced remote sensing technologies and sophisticated data processing techniques, this study offers a methodological framework that enhances the precision and depth of environmental analysis. The core methodology involves the systematic processing of satellite data, including radiometric and geometric corrections, combined with the use of analytical indices such as the Normalized Difference Water Index (NDWI) and the Enhanced Vegetation Index (EVI). These indices play a crucial role in accurately delineating water bodies and assessing the extent of flooding. The approach not only improves the reliability of flood mapping but also contributes to the broader understanding of environmental changes and aids in effective disaster management. Through this study, we demonstrate how strategic data integration can provide valuable insights for policymakers, enhancing responses to environmental crises.